Does sociality drive diversity and composition of airway microbiota in cetaceans?. Issue 3 (31st March 2020) - Vendl, Catharina; Slavich, Eve; Nelson, Tiffanie; Acevedo‐Whitehouse, Karina; Montgomery, Kate; Ferrari, Belinda; Thomas, Torsten; Rogers, Tracey
Summary: The number of social contacts of mammals is positively correlated with the diversity of their gut microbes. There is some evidence that sociality also affects microbes in the respiratory tract. We tested whether the airway microbiota of cetacean species differ depending on the whales' level of sociality. We sampled the blow of blue ( Balaenoptera musculus ), grey ( Eschrichtius robustus ), humpback ( Megaptera novaeangliae ) and long‐finned pilot whales (PWs) ( Globicephala melas ) and analysed the blow microbiota by barcode tag sequencing targeting the V4 region of the bacterial 16S rRNA gene. Humpback whales (HWs) show higher levels of sociality than blue (BW) and grey (GW), while PWs are the most gregarious among the four species. The blow samples of the HWs showed the highest richness and diversity. HWs were also the only species with a species‐specific clustering of their microbial community composition and a relatively large number of core taxa. Therefore, we conclude that it cannot be sociality alone shaping the diversity and composition of airway microbiota. We suggest the whale species' lung volume and size of the plume of exhaled air as an additional factor impacting the transmission potential of blow microbiota from one individual whale to another.